1976
DOI: 10.1161/01.res.38.6.502
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced aldosterone response to angiotensin II in human hypertension.

Abstract: SUMMARY Adrenal and vascular responsiveness to graded doses of angiotensin II (A II) were recorded for seven normal subjects and 12 patients with essential hypertension while in balance on an intake of 200 mEq sodium/100 mEq potassium. Patients with essential hypertension had been previously studied and known to have normal responses of plasma renin activity to sodium restriction and upright posture. A l l was administered for 30 minutes at rates of 0.1, 0.3, 1, and 3 ng/kg per minute and plasma aldosterone re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
1

Year Published

1979
1979
2002
2002

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 21 publications
3
37
1
Order By: Relevance
“…However, our findings suggest that this difference in aldosterone dynamics may be related to altered sensitivity of the adrenal cortex to changes in circulating angiotensin levels, because the ratio of the percentage changes of PA to those of PRA was significantly higher in the normotensive group than in the hypertensive group. This finding is compatible with the results of Kish et al,28) who demonstrated that responses of PA to infused angiotensin II were elevated in patients with essential hypertension who were on a diet containing 200mEq of sodium and 100mEq of potassium per day. Also, Wisgerhof et al29) reported that the response of aldosterone secretion to infused angiotensin II was enhanced in patients with low-renin essential hypertension.…”
Section: Discussionsupporting
confidence: 92%
“…However, our findings suggest that this difference in aldosterone dynamics may be related to altered sensitivity of the adrenal cortex to changes in circulating angiotensin levels, because the ratio of the percentage changes of PA to those of PRA was significantly higher in the normotensive group than in the hypertensive group. This finding is compatible with the results of Kish et al,28) who demonstrated that responses of PA to infused angiotensin II were elevated in patients with essential hypertension who were on a diet containing 200mEq of sodium and 100mEq of potassium per day. Also, Wisgerhof et al29) reported that the response of aldosterone secretion to infused angiotensin II was enhanced in patients with low-renin essential hypertension.…”
Section: Discussionsupporting
confidence: 92%
“…7 *~M Such subjects are of special interest in this context because they permit an evaluation of the effects of sodium depletion on the aldosterone response to angiotensin II in the absence of changes in the endogenous plasma angiotensin II concentration, and hence may reveal adrenocortical sensitizing mechanisms that are independent of the renin-angiotensin system. In a series of six anephric patients studied by Deheneffe et al, 84 sodium depletion led to highly significant enhancement of the response of plasma aldosterone to infused angiotensin II, although this response remained distinctly below that of normal subjects.…”
Section: Mechanism Of Shift In Angiotensin Ii-aldosterone Curvementioning
confidence: 99%
“…An important point of distinction is that the response of aldosterone to infused angiotensin II is subnormal in Conn's syndrome (Mason et al, 1978;Brown et al, 1979). Thus in terms of their response, to angiotensin II, idiopathic hyperaldosteronism, low-renin hypertension, and essential hypertension are similar to each other but markedly different from Conn's syndrome (Table 2, see also Kisch et al, (1976), Brown and Wisgerhof (1978), Davies et al, (1979) andBrown et al (1979)). …”
Section: Abnormal Relation Of Angiotensin II and Aldosterone In Essenmentioning
confidence: 97%
“…The response of aldosterone to infused angiotensin II is also abnormally brisk (Kisch et al, 1976;Wisgerhof and Brown, 1978;Brown et al, 1979;Davies et al, 1979). Our own data show that for a given plasma concentration of angiotensin II, and for a given increment in plasma concentration, aldosterone increases more in essential hypertension than it does in normal subjects (Fig.…”
Section: Abnormal Relation Of Angiotensin II and Aldosterone In Essenmentioning
confidence: 99%